The Mediating Effect of Self–Efficacy on the Relationship Between Goal Setting and Academic Motivation among College Students in Mathematics - Ismael W. Baog; El Rhea Mae D. Tura; Al-Cris Seban (International Journal of Educational Research, 2025)
Academic motivation in mathematics remains a critical factor influencing student engagement and performance. This study examined the mediating effect of self-efficacy on the relationship between goal setting and academic motivation among college students. Using mediation analysis, 100 participants were selected through stratified random sampling. Results indicated that self-efficacy partially mediates the relationship, but goal setting unexpectedly had a negative effect on self-efficacy, suggesting that specific goal-setting strategies may introduce pressure or unrealistic expectations. This finding challenges the assumption that goal setting always enhances confidence and motivation. Future research may explore alternative mediating factors and variations in goal-setting strategies. Additionally, educational interventions should integrate self-efficacy-enhancing techniques such as mastery experiences and peer support to maximize student motivation and achievement in mathematics.